ANALISIS KINERJA PRODUKSI, EKSPOR DAN IMPOR KOMODITAS KOPI INDONESIA DI ERA REFORMASI - Darkiman Ruminta - (Politeknik Bisnis Indonesia, 2023)
This study aims to analyze the production, export and import performance of Indonesian coffee commodities. The data in this study is secondary data obtained from various government agencies. The method of analysis uses a qualitative description with Microsoft Excel Software. The results of the analysis found that the production, export and import performance of Indonesian coffee commodities during the Reform Order was generally quite good and on an annual average experienced positive growth. The development of the volume of exports and imports of Indonesian coffee commodities fluctuates every year. Part of domestic coffee production is consumed and partly exported abroad. The volume of Indonesian coffee exports during the 1998-2021 period averaged 388,147 tons/year or around 59 percent of the average national coffee production, which produced 665,213 tons/year. Meanwhile, the average volume of Indonesian coffee imports during the 1998-2021 period reached 18,765 tons/year. Indonesia's coffee trade balance is always a surplus, meaning that the volume and value of exports are always greater than the volume and value of imports.